2012
DOI: 10.3952/physics.v52i3.2473
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical features of dielectrical nano-barrier layers in CdSe<sub>x</sub>S<sub>1-x</sub> films formed by screen printing method

Abstract: The thermal activation process of CdSe x S 1-x films, formed by screen printing, was investigated. We mostly focused on the influence of thermal treatment conditions on oxidised film formation on the crystalline grain surface with nano-barrier "dielectric-semiconductor" layer generation. The composition and thickness of nanobarrier layers were determined by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) methods. The thickness of nano-barrier layers was found to be 2-5 monolayers. It was sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The experimental studies [1][2][3] showed that the modes of applying the films onto the polycrystalline glass substrates by screen printing, while choosing a particular web to apply the paste to a substrate, require considering the functional purpose of the applied film. The size of the gap between the stencil and the substrate was selected by varying the sizes of the gap (0.5-4 mm) between the stencil and the substrate during the film deposition.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The experimental studies [1][2][3] showed that the modes of applying the films onto the polycrystalline glass substrates by screen printing, while choosing a particular web to apply the paste to a substrate, require considering the functional purpose of the applied film. The size of the gap between the stencil and the substrate was selected by varying the sizes of the gap (0.5-4 mm) between the stencil and the substrate during the film deposition.…”
Section: Resultsmentioning
confidence: 99%
“…The microstructure of CdS 1−x Se x -based films and their most important properties (photoconductivity, luminescence, etc.) depend largely on the type and concentration of precursors, film production technology, and thermal activation of photoconductivity [1][2][3][4]. During thermal activation, the crystallites of films are oxidized, as a result of which, an oxide phase-semiconductor barrier is formed on their surface, the parameters of which can be controlled by optimizing the processing temperature range and the gas medium composition, as well as the composition of the applied pastes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations